ARTISTIC ORIGINALITY OF D. RUBINA'S STORY THE DOG - Кравченко К. А. (Journals Park Publishing, 2025)
The article analyzes the artistic world in the story "The Dog" by D. Rubina. The author's attention is focused on sensory poetics, the specifics of extra-plot elements, symbolism, coloristics and landscape, onomastics.
Keywords: Artistic world, symbolism, coloristics, landscape, onomastics.